Implications of Key Philosophical Assumptions and Paradigms in Geography Teaching and Research - Sapkota, Kanhaiya; Paudyal, Narayan Prasad (The Third Pole: Journal of Geography Education, 2021)
Geography has had limited interchange with the implications of major philosophical assumptions and paradigms in geographical education and research methodology. This paper claims a closer engagement with the philosophical arguments on ontology, epistemology, and axiology as well as the research and teaching strategies or paradigms. It is adopted and has much to offer to geography, not least in providing a showground within which very different types of geographical inquiry i.e., qualitative and quantitative, may find some common ground for helpful discussion and debate in geographic research. Nevertheless, this will only be fully accomplished if geography enters on: (1) studies that develop and arrange clear positivist ideas and concepts within the particular geographic research; (2) studies that attempt to relate geographic research to the broader realm of the constructionism/ interpretivism tradition; and (3) examination of the link of the geographic research with the pragmatism. The contemporary revival of geographic paradigm is described, together with its impacts on research and teaching methodology in geography. The prevailing literature on geographical rendezvous with positivism is then examined, and it is claimed that there is a single reality, which can be measured and known. Therefore, they are more likely to use quantitative methods to measure the fact. Likewise, constructivist believe that there is no single reality or truth. Thus, existence need to be interoperated, and consequently they are more likely to use qualitative methods to get those multiple realities. Pragmatism has much broader relevance within both physical and human geography, not linked to particular research styles. It believes that truth or reality is constantly negotiated, debated, interpreted and therefore, the best method to use is to solve the problem or explores the truth or fact.